Aplikasi Pendukung Keputusan Perbaikan Serta Penyedia Jasa Service Komputer Dan Laptop Menggunakan Metode NaÃ¯ve Bayes - Rifki Pramoendhito Putra; Subari Subari; Siti Aminah (LPPM STIKI MALANG, 2021)
Computers and laptops are hardware devices that are often used for student learning activities at school. Both ordinary learning activities and used for examinations, be it regular exams or national exams. A developing learning system should be balanced with good equipment with the addition of good operator personnel. Problems arise if the device used by students is damaged and is compounded by the operator's inability to solve problems that arise immediately. NaÃ¯ve Bayes was chosen as a classification method to determine damage based on the probability of symptoms occurring. The creation of a structured repair solution from external to internal factors that is easy for users to understand is also very necessary to support success in the repair process independently. This study took a case study at SMP Negeri 2 Mojosari which is located on Jalan S. Parman Ds. Modopuro Kec. Mojosari Kab. Mojokerto - East Java, where in the school institution data will be collected in the form of information about symptoms of computer / laptop damage and frequent damage and determination of repair solutions.